CYTOPLASMIC NUCLEAR MALE STERILITY IN SORGHUM (Sorghum bicolor (L.) MOENCH) – CURRENT STATUS AND FUTURE PROSPECTS - REDDY, P. SANJANA (The Journal of Research, PJTSAU, 2019)
Discovery of cytoplasmic nuclear male-sterility has revolutionized sorghum production. As a result of extensive breeding efforts, hybrids are available for sorghum cultivated for diverse uses such as grain sorghum, sweet sorghum and forage sorghum. Almost all the hybrids are based on A1 CMS system. In order to have an alternate source in case of vulnerability of cytoplasm to any disease in future, there is a need to diversify the cytoplasm base. In addition to the A1, several other cytoplasmic sources, like A2, A3, A4,A5, A6, 9E and KS cytoplasms differing from each other were identified. The alternate cytoplasms have been characterized and studied for grain yield and agronomic traits, resistance to pests and diseases and the outcome of the research are presented.